A genetic linkage map and improved genome assembly of the termite symbiont Termitomyces cryptogamus - Vreeburg, Sabine M. E.; Auxier, Ben; Jacobs, Bas; Bourke, Peter M.; van den Heuvel, Joost; Zwaan, Bas J.; Aanen, Duur K. (BMC genomics, 2023)
The termite-fungus symbiosis is an ancient stable mutualism of two partners that reproduce and disperse independently. With the founding of each termite colony the symbiotic association must be re-established with a new fungus partner. Complementarity in the ability to break down plant substrate may help to stabilize this symbiosis despite horizontal symbiont transmission. An alternative, non-exclusive, hypothesis is that a reduced rate of evolution may contribute to stabilize the symbiosis, the so-called Red King Effect. To explore this concept, we produced the first linkage map of a species of Termitomyces, using genotyping by sequencing (GBS) of 88 homokaryotic offspring. We constructed a highly contiguous genome assembly using PacBio data and a de-novo evidence-based annotation. This improved genome assembly and linkage map allowed for examination of the recombination landscape and its potential effect on the mutualistic lifestyle. Our linkage map resulted in a genome-wide recombination rate of 22 cM/Mb, lower than that of other related fungi. However, the total map length of 1370 cM was similar to that of other related fungi. The apparently decreased rate of recombination is primarily due to genome expansion of islands of gene-poor repetitive sequences. This study highlights the importance of inclusion of genomic context in cross-species comparisons of recombination rate.